Typology and Narrative Structure of Tembang Mamaca: An Oral Literature Study in Pamekasan, Madura - Mas'odi Mas'odi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
The mamaca tradition represents a unique form of Madurese oral literature, embodying both Islamic values and local cultural wisdom. Despite its richness, scholarly studies have paid limited attention to the typology of its verse songs (tembang) and the narrative structures embedded within the performances, leaving a gap in understanding its literary and cultural significance. This study aims to analyze the typological characteristics of tembang and to uncover the narrative frameworks that structure mamaca as both a performance and a cultural text. Using a qualitative-descriptive method with an oral literature approach, the research was conducted in Bandaran Village, Pamekasan Regency. Data were collected through participant observation, in-depth interviews with local performers, and textual analysis of mamaca manuscripts. The findings reveal six principal tembang—Artate, Kasmaran, Durma, Salangit, Pangkur, and Sinom—each marked by distinctive thematic content and narrative patterns. These tembang not only articulate aesthetic expression but also encapsulate moral and religious teachings, conveyed through symbolic language and dialogic performance. The narrative structures highlight oppositional and complementary patterns that sustain both entertainment and didactic purposes. This study contributes to the field of oral literature by demonstrating how mamaca operates as an adaptive and transgenerational medium of cultural preservation, character education, and spiritual transmission. It underscores the importance of examining local oral traditions as dynamic systems of meaning that continue to shape communal identity in Madura.